Foraging routines and estimated daily food intake in Barnacle Geese wintering in the northern Netherlands - Ebbinge, Barwolt; Canters, Kees; Drent, Rudolf (Wildfowl, 1975)
The Barnacle Goose Branta leucopsis in winter, according to observations made in the northern Netherlands in the 1972-1973 season, consumes 135-158 gm (dry weight) of grass daily, equivalent to 602-703 kcal, and retains approximately 34% (i.e., metabolized energy = 205-239 kcal). This rough estimate, indicating that wild geese daily expend an amount of energy that can be expressed as twice their basal metabolic rate, was derived from the following information. (a) The Barnacle Goose produces 160 droppings per day, (b) a dropping weighs 0.66 gm dry, (c) analysis of crude fibre and of cellulose in samples of both droppings and the grass the geese were feeding on, with the assumption that these components are undigestible, indicates that 21.7-33.2% (dry weight) of the food ingested is retained, the remainder being rejected as droppings, (d) the caloric value of grass was 4.46, of droppings 4.38 kcal/gm dry weight. Since our grass samples were clipped samples disregarding the effects of selectivity by the geese (for instance the preference for grass tips which have a lower cellulose content than the plants as a whole) the weak link is likely to be (c), and we expect our value to be an underestimate. Comparison with several theoretical expectations, and with results (most of them equally crude) from studies on other wild birds, does suggest, however, that our estimate is reasonably close to the mark. In our study area the Barnacle Goose relies heavily on intensely managed pastureland for its winter foraging (66% of all goose-days were spent on grassland grazed by sheep or cattle). In the course of the winter the geese utilized a number of areas in succession, and from transects where the cumulative number of droppings was determined, it was found that the geese tended to abandon an area when approximately 2,600 goose-days had accumulated per hectare. Utilization was, however, not evenly distributed, the least disturbed sectors reaching grazing pressures far in excess of this. Further work will be required to link this empirical figure for carrying capacity, equivalent to a consumption of 40 gm dry matter per square metre, with the amount of living matter available (approximately 100 gm per square metre at the beginning of the winter).